2011
DOI: 10.1117/12.889675
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable bactericidal effects from novel silica-coated silver nanoparticles

Abstract: The enhancement of the electromagnetic field in the surroundings of nanoparticles via surface plasmon resonance offers promising possibilities for biomedical applications. Here we report on the selective triggering of antibacterial activity using a new type of silver nanoparticles coated with silica, Ag@silica, irradiated at their surface plasmon frequency. The nanoparticles are able to bind readily to the surface of bacterial cells, although this does not affect bacterial growing since the silica shell largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Panas et al [19] reported that excitation of Ag/TiO 2 NPs by blue laser light at 455 nm for 5 min inhibited the proliferation of Streptococcus salivarius due to high photocatalytic activity that irreversibly damages cell walls and membranes. In another study, Fuertes et al [20] analyzed the antibacterial activity of Ag-NPs coated with porous silica and irradiated at their SPR frequency of 387 nm, which induced production of toxic ROS and subsequent cell death in E. coli. They suggested that a possible mechanism for the synergistic effect of Ag-NPs with laser light is the production of cytotoxic ROS by the visible blue light resulting in destruction of the bacterial cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Panas et al [19] reported that excitation of Ag/TiO 2 NPs by blue laser light at 455 nm for 5 min inhibited the proliferation of Streptococcus salivarius due to high photocatalytic activity that irreversibly damages cell walls and membranes. In another study, Fuertes et al [20] analyzed the antibacterial activity of Ag-NPs coated with porous silica and irradiated at their SPR frequency of 387 nm, which induced production of toxic ROS and subsequent cell death in E. coli. They suggested that a possible mechanism for the synergistic effect of Ag-NPs with laser light is the production of cytotoxic ROS by the visible blue light resulting in destruction of the bacterial cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…LSPR leads to the appearance of strong absorption bands, the enhancement of the electromagnetic (EM) field near the nanoparticles and the appearance of scattering to the far field [1,5]. Beyond some known decorative applications [6,7], plasmonic effects are important in a wide range of technological domains, which include plasmon-based photodetectors [8] and modulators [9], gas sensors [10][11][12], biosensors [13][14][15], photothermal therapy [16], photodynamic therapy [17], LSP-enhanced solar cells [18,19], surface enhanced Raman spectroscopy (SERS) [20][21][22], plasmonic nanoscopy [23], thermal emitters [24], light-emitting diodes [25] and magnetic storage [26].…”
Section: Introductionmentioning
confidence: 99%